Growth performance, body composition and fatty acid profile of liver and muscle in tilapia, Oreochromis mossambicus (Peters, 1852) fed algal meal incorporated diets - Patra, S. K.; Mishra, K.; Patro, B.; Samantaray, K.; Khuntia, B. K.; Sahu, B.; Tripathy, M. K. (Indian Journal of Fisheries, 2018)
The present study was conducted to evaluate the effect of algal meal incorporated diets on the growth performance and fatty acid profile of tilapia Oreochromis mossambicus (Peters, 1852). Control diet (Diet 1) for the study was formulated with rice bran, groundnut oil cake (GNOC) and soybean meal. Six iso-energetic and iso-nitrogenous test diets (Diets 2 to 7) were prepared by incorporating (@40%) one of the four microalgae viz., Anabaena cylindrical (AN; Nostoc salbasa (NS); Spirulina platensis (SP) and Westiellopsis prolifica (WS) or with an algal meal mixture containing the above four algae plus the macroalgal species viz., Gracilaria edulis (GE) and Enteromorpha intestinalis (EI) mixed in equal proportions along with sunflower oil and cod liver oil, (by totally replacing rice bran, GNOC and soyabean meal of the control diet) (AMM+O diet, Diet 6) and AMM without addition of oils served as AMM diet (Diet 7). The algal meal supplemented diets were tested against a control diet to find out their suitability for culture of tilapia fingerlings. The fish (av. wt. 2.8 Â± 0.4 g) were fed up to satiation for 56 days at 28Â±20C. Significant (p< 0.05) enhancement in growth was observed with AN (565.2%) diet followed by SP (500.0%) and WS (400%) compared to control (402.3%). The AN diet showed best performance in terms of feed conversion ratio (FCR), protein efficiency ratio (PER) and specific growth rate (SGR) while AMM diet showed least efficiency. Fish fed with SP diet showed better apparent net protein utilisation (ANPU%) as compared to other diets. Saturated fatty acid (SFA) in the liver and muscle decreased while monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids increased over their respective initial values in all the dietary groups except in groups fed with AMM+O and AMM. The n-6 level of liver and muscle increased with SP diets. Substantial increase in docosahexaenoic acid (DHA, 22:6n3) and eicosapentaenoic acid (EPA, 20:5n3) in fish fed with WS emphasised the benefits of its use as dietary ingredients for tilapia. The results clearly indicated that algae like AN and SP incorporated in tilapia diet significantly enhance growth and carcass protein, whereas WS helps to improve the levels of the essential n-3 fatty acids (EPA and DHA).